Comparison of outcomes between symptomatic and asymptomatic patients with colorectal cancer: a propensity score-matched analysis of surgical invasiveness, medical costs and oncological outcomes. Issue 1 (17th July 2017) - Inada, Ryo; Nagasaka, Takeshi; Watanabe, Ayako; Yagi, Tomohiko; Mori, Yoshiko; Kondo, Yoshitaka; Kishimoto, Hiroyuki; Umeda, Yuzo; Fujiwara, Toshiyoshi
Abstract : Background and aims: Whether asymptomatic patients with colorectal cancer (CRC) who are treated in hospitals show better outcomes than symptomatic patients with CRC still remains unknown. The aim of this study was to evaluate differences in clinical benefits following treatment in asymptomatic and symptomatic patients with CRC. Methods: This study was a retrospective cohort analysis with data obtained from records. A cohort of 145 asymptomatic and 123 symptomatic patients who underwent CRC surgery between January 2009 and December 2011 was enrolled. To reduce bias in comparing outcomes, propensity score (PS) analysis was used for matching of patients in the symptomatic and asymptomatic groups based on clinicopathological factors. Surgical invasiveness, medical costs and oncological outcomes were examined by unadjusted and PS-matched analysis. Results: Tumours in the symptomatic group were more often diagnosed in advanced stages compared with tumours in the asymptomatic group. Therefore, fewer symptomatic group patients underwent minimally invasive surgery. Short-term outcomes, including amount of blood loss, duration of postoperative hospital stay and perioperative medical costs, were significantly better in the asymptomatic group. Although overall survival was significantly better in the asymptomatic group, there was no significant difference between the groups when the patients were adjusted on the basis of PS. Conclusions: Though this study was limited by the retrospective nature and small sample size, favourable outcomes in asymptomatic patients were due to the higher proportion of patients in this group who were diagnosed with CRC in earlier stages, due to participation in CRC screening programmes.